THE ROLE OF SUPPLY CHAIN INTEGRATION IN CREATING TOURIST LOYALTY - Sukati, Inda; Sanyal, Shouvik; Awaain, Ali Mohsin Ba (International Journal of Supply Chain Management, 2020)
Abstractâ??The tourism industry involved various industry such as transportation industry, food and beverages industry, hospitality industry, and many other related industries. The main purpose of this study was to investigate the linkage between tourism supply chain integration with tourist satisfaction and loyalty. The target respondents in this study are tourists come Oman for tourist purpose stop at Salalah International airport, stay at hotels, apartments, and visit major tourist locations and shopping centres. In this research, the following outcomes were obtained: The correlation analysis showed that (1) Tourism internal firm integration is related to tourist satisfaction. Tourism firm-supplier integration is related to tourist satisfaction, (3) Tourism firm-customer integration is related to tourist satisfaction. The result also show that tourist satisfaction related to tourist loyalty. Keywords: tourism supply chain integration, Satisfaction, Loyalty